Development of android-based weapon monitoring application in the armory - Sadewa, Rio Bintang; Saragih, Hondor; Lediwara, Nadiza (Institute of Computer Science (IOCS), 2024)
Information and communication technologies (ICT) are of vital importance in the context of modern military operations, with Android-based solutions becoming increasingly relevant for the improvement of military weapons management systems. This study addresses the inefficiencies of current manual weapon management practices, which are susceptible to data errors and operational delays. The objective of this research is to enhance the accuracy, efficiency, and security of weapon management through the development of an Android-based monitoring application. The Rapid Application Development (RAD) methodology was employed to streamline the development process, which entailed the planning of requirements, the design of the user interface, the construction of the application, and its implementation. The application was constructed using Kotlin for the front end and Node.js with Express.js for the back end. It integrates real-time data updates, automated notifications, and efficient data management. The system’s design incorporates a comprehensive class diagram for database structure, user interface mockups, and various backend components, including models, migrations, controllers, routing, and middleware. The results demonstrate that the application markedly enhances weapon management by reducing manual errors, increasing operational efficiency, and providing enhanced security and accountability through accurate, real-time digital record-keeping.